Family-related employment interruptions and self-employment of women: Does policy matter? - Olga Suprinovič; Stefan Schneck; Rosemarie Kay (Institut für Mittelstandsforschung (IfM) Bonn, 2015)
This paper analyzes how statutory entitlements to maternity or parental leave affect female entry into self-employment after childbirth. For our estimations we use comprehensive panel data for German adults born between 1944 and 1989. We find that utilization of statutory parental leave decreases women's probability to switch into self-employment. This effect is statistically significant for start-ups in highskilled occupations. In contrast, start-ups in low-skilled occupations are not significantly affected by statutory parental leave. – – Der Aufsatz untersucht, wie sich familienbedingte Erwerbsunterbrechungen auf die Gründungsneigung von Frauen auswirken. Hierfür wurden Paneldaten für die Erwachsenenbevölkerung in Deutschland (Geburtsjahrgänge 1944 bis 1989) ausgewertet. Das Ergebnis: Gesetzlich geregelte familienbedingte Auszeiten reduzieren signifikant die Wahrscheinlichkeit, dass eine Frau sich in einem hochqualifizierten Tätigkeitsbereich selbstständig macht. Für Gründungen in den gering qualifizierten Bereichen konnte ebenfalls ein negativer, jedoch nicht signifikanter Effekt solcher Erwerbsunterbrechungen nachgewiesen werden.
Keywords: J16; J18; L26; M13; 330; family policy; parental leave; women's self-employment